Efeito de vídeos educativos da plataforma safety4me® no conhecimento, na atitude e prática de pessoas com doença renal crônica sobre segurança do paciente - Lima, Magda Milleyde de Sousa (2024)
Patient safety is a global concern, with immense challenges to promote quality and safe care. In hemodialysis clinics, patients with chronic kidney disease are typically vulnerable to episodes that jeopardize their health security, especially due to the treatment process that involves high rates of interventions. In this context, engaging patients and their families in promoting safety allows patients to better understand their reality, the disease, the treatment they undergo, and safe care practices during this treatment. This study aimed to evaluate the effectiveness of the Safety4me® Platform on the knowledge, attitudes, and practices of individuals with chronic kidney disease regarding patient safety in hemodialysis clinics. A multimethod study was conducted, consisting of two methodological approaches (construction and validation of educational videos on patient safety and construction and validation of scales on knowledge, attitudes, and practices regarding patient safety) and a quasi-experimental approach (effectiveness of the Safety4me® Digital Platform on the knowledge, attitudes, and practices of individuals with chronic kidney disease undergoing hemodialysis treatment). The study was conducted in two hemodialysis clinics in Ceará, Brazil. The final version of the educational videos on patient safety resulted in the production of seven distinct videos covering the following topics: correct patient identification, communication among healthcare professionals, safe medication administration, surgical care related to fistula creation and catheter insertion, infection prevention, and fall prevention. In the content analysis, the majority of items showed agreement above 0.8, being considered valid. Regarding appearance validation, all items achieved agreement above 0.8. The target audience evaluation revealed that, of the 14 items analyzed, 11 showed agreement above 0.8. For the Knowledge, Attitude, and Practice Scale, all items presented Content Validity Coefficients above 0.8, being considered valid. Factor analysis revealed a structure with two latent factors. The results of the effectiveness analysis of the educational videos indicated statistically significant differences for all investigated variables in both clinics, with pre-intervention results lower than post- intervention results. Thus, the educational videos are a valuable tool for promoting patient safety in hemodialysis clinics.